2014
DOI: 10.4103/0974-9233.129776
|View full text |Cite
|
Sign up to set email alerts
|

Autologous serum for anterior tissue necrosis after porous orbital implant

Abstract: Orbital implants are now routinely used after enucleation and evisceration. However exposure of the implant can lead to infection and extrusion. Hence, early repair of larger exposure with graft material is required. We describe three cases where early postoperative mucosal dehiscence was successfully managed with autologous serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…CBS is considered a reliable source of undifferentiated mesenchymal stem cells [ 106 , 107 ], which are self-renewal elements that are able to replace directly corneal keratocytes [ 104 ] and conjunctival, limbal [ 76 ], and retinal nerve cells [ 104 ]. In addition, CBS contains consistent levels of cytokines, GFs, fibronectin, prealbumin, and fatty oils that provide useful instruments for corneal differentiation [ 74 , 108 ]. Moreover, CBS includes antibacterial agents as IgG, lysozyme, and complement but lower levels of vitamin A compared to peripheral serum [ 109 ].…”
Section: Clinical Applications and Study Resultsmentioning
confidence: 99%
“…CBS is considered a reliable source of undifferentiated mesenchymal stem cells [ 106 , 107 ], which are self-renewal elements that are able to replace directly corneal keratocytes [ 104 ] and conjunctival, limbal [ 76 ], and retinal nerve cells [ 104 ]. In addition, CBS contains consistent levels of cytokines, GFs, fibronectin, prealbumin, and fatty oils that provide useful instruments for corneal differentiation [ 74 , 108 ]. Moreover, CBS includes antibacterial agents as IgG, lysozyme, and complement but lower levels of vitamin A compared to peripheral serum [ 109 ].…”
Section: Clinical Applications and Study Resultsmentioning
confidence: 99%
“…A recently published case series reported that autologous serum promoted wound healing and prevented tissue necrosis after PP implantation. 40 Autologous PL may be used to prevent tissue necrosis and PP implant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Autologous serum has been used over the last two decades to promote the healing of epithelial and cartilaginous damage of both known and unknown aetiologies. 13,[29][30][31] At the same time, it includes various immunoglobulins (e.g. immunoglobulin G and immunoglobulin A) and lysozyme.…”
Section: Discussionmentioning
confidence: 99%